2019
DOI: 10.1111/anu.12918
|View full text |Cite
|
Sign up to set email alerts
|

Effect of substituting fishmeal with corn protein concentrate on growth performance, nutrient utilization and skin coloration in red hybrid tilapia, Oreochromis sp.

Abstract: The objective of this study was to evaluate the effects of fishmeal (FM) replacement with corn protein concentrate (CPC) on growth performance, nutrient utilization, gut morphology and skin coloration of red hybrid tilapia, Oreochromis sp. Five isonitrogenous (350 g/kg crude protein) and isolipidic (10 g/kg lipid) diets were formulated to contain CPC that substituted 0%, 25%, 50%, 75% or 100% FM. Diets were fed to triplicate groups of tilapia (mean initial weight, 10.33 ± 0.02 g) twice daily for 63 days. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
33
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(40 citation statements)
references
References 33 publications
(53 reference statements)
5
33
0
2
Order By: Relevance
“…The results of our study declared that lightness value decreased in diets containing CPC compared with the control group, which coincided with Herath et al 2016 of those fish fed with dietary CPC can be explained by the high content of carotenoids, especially lutein and zeaxanthin in corn (Scott & Eldridge, 2005). In similar studies, fish fed with CPC and CGM had high a * value in the fillet of red hybrid tilapia and rainbow trout (Ng et al, 2019;Saez et al, 2016).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results of our study declared that lightness value decreased in diets containing CPC compared with the control group, which coincided with Herath et al 2016 of those fish fed with dietary CPC can be explained by the high content of carotenoids, especially lutein and zeaxanthin in corn (Scott & Eldridge, 2005). In similar studies, fish fed with CPC and CGM had high a * value in the fillet of red hybrid tilapia and rainbow trout (Ng et al, 2019;Saez et al, 2016).…”
Section: Discussionsupporting
confidence: 91%
“…In a similar study, Ng et al (2019) reported that substitution fishmeal with CPC up to 50% in the diet of red hybrid tilapia had no adverse effects on the growth performance and feed efficiency.…”
Section: Discussionmentioning
confidence: 84%
“…Plant protein origins have advantages in price, stable supply, and nutritional composition (Daniel, 2018;Gatlin et al, 2007). A wide range of plant protein ingredients such as soybean (Murashita et al, 2018;Ye et al, 2019;Zhang et al, 2018), corn gluten (Gerile & Pirhonen, 2017), corn-protein concentrate (Ng, Leow, & Yossa, 2019), wheat gluten (Monge-Ortiz et al, 2016), rapeseed (Dossou et al, 2018), peas (Nogales-Mérida, Tomás-Vidal, Moñino-López, Jover-Cerdá, & Martínez-Llorens, 2016), canola (Thiessen, Maenz, Newkirk, Classen, & Drew, 2004), cottonseed (Pham et al, 2008;Pham, Lee, Lim, & Park, 2007), and rice distillers' dried grain (Bae, Kim, & Lee, 2015) have been explored as FM alternatives in aquafeed. However, the presence of antinutritional factors or nutritional imbalance in the plant proteins that might negatively affect fish growth, gut microbiota composition, immune response, and survivability (Desai et al, 2012;Liang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Dessa forma, pesquisas para a incorporação de ingredientes alternativos para a alimentação aquática vêm sendo realizadas (SHAHIDI e AMBIGAIPALAN, 2015;SHAH, et al, 2018;NG et al, 2019;ZETTL et al, 2019). Neste contexto, o rejeito de pesca é uma fonte abundante de proteína que pode torna-se um ingrediente alternativo na aquicultura, além de oferecer um destino economicamente viável para a fauna acompanhante.…”
Section: Introductionunclassified